The Effect of Company Growth, Firm Size, DPS and Profitability on Firm Performance in LQ45 Companies - Jovianto Jovianto; Johny Budiman (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Firm performance is a ratio used to evaluate a company's growth and future potential by collecting information related to the company's earnings to help assess whether there is a possibility of changes in the company's economy. Based on the characteristics of the problem, this study includes comparative historical and causal research. In this study, the object studied, namely the LQ45 index. This study used purposive sampling as a data collection method. This descriptive statistical data was tested using secondary data with the object of research of companies included in the LQ45 index list and having financial statements for five consecutive years from 2017-2021. Companies listed in the LQ45 index for five consecutive years from 2017-2021 are 27 companies and this data meets the criteria for conducting research. For companies that are not included in the criteria to be sampled, there are as many as 18 companies. So, the final sample number of companies taken is 27 companies with a total data of 135 companies. This study examines the effect of Capital Structure on Firm Performance in LQ45 companies with a total of 45 companies listed on the IDX for the period 2017 – 2021 that meet the criteria of having annual financial statements for five consecutive years. words: Firm performance; LQ45 index; Annual Financial Report